2020
DOI: 10.1212/wnl.0000000000010951
|View full text |Cite|
|
Sign up to set email alerts
|

Apathy and risk of probable incident dementia among community-dwelling older adults

Abstract: ObjectiveTo evaluate the association between baseline apathy and probable incident dementia in a population-based sample of community-dwelling older adults.MethodsWe studied 2,018 white and black community-dwelling older adults from the Health, Aging, and Body Composition (Health ABC) study. We measured apathy at year 6 (our study baseline) with the modified Apathy Evaluation Scale and divided participants into tertiles based on low, moderate, or severe apathy symptoms. Incident dementia was ascertained over 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Another longitudinal study on cognitively normal individuals reported that of those who progressed from being normal to MCI or dementia, more than 59% developed NPSs before the diagnosis of any cognitive disorder ( Wise et al, 2019 ). A recent study involving community-dwelling adults showed an association of apathy with an increased risk of developing probable dementia ( Bock et al, 2020 ). Therefore, MBI is becoming increasingly recognized as a prodromal stage of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Another longitudinal study on cognitively normal individuals reported that of those who progressed from being normal to MCI or dementia, more than 59% developed NPSs before the diagnosis of any cognitive disorder ( Wise et al, 2019 ). A recent study involving community-dwelling adults showed an association of apathy with an increased risk of developing probable dementia ( Bock et al, 2020 ). Therefore, MBI is becoming increasingly recognized as a prodromal stage of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that apathy increases with age (Brodaty et al, 2010) and is associated with poor outcomes in older adults, such as difficulties in daily functioning and decreased quality of life (Tierney et al, 2018). Growing evidence indicates a link between apathy and incident dementia in healthy older adults (van Dalen et al, 2018;Bock et al, 2020) and provides support for the hypothesis that apathy may be a prodromal feature of Alzheimer's disease spectrum (Munro et al, 2015). These findings highlight the need to investigate the association between apathy and brain changes that have unfavorable implications for healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…We do not know why this happens, whether it is the final stages of our development through a comprehensive isomorphic representation and the belief that we know the answers already, or whether it is emotional, related to the loss of zest for life. One of the most consistent findings in the etiology of dementia is the emerging expression of apathy and depression as a prodrome of dementia [100], [101]. Apathy and depression highlight a perceptual change [102] with longterm consequences.…”
Section: Discussionmentioning
confidence: 99%